Immune gene expression and genome-wide association analysis in rainbow trout with different resistance to Yersinia ruckeri infection. Issue 106 (November 2020) - Zuo, Shaozhi; Karami, Asma M.; Ødegård, Jørgen; Mathiessen, Heidi; Marana, Moonika H.; Jaafar, Rzgar M.; von Gersdorff Jørgensen, Louise; Abdu, Mohamed; Kania, Per W.; Dalsgaard, Inger; Nielsen, Torben; Buchmann, Kurt
Abstract: Selective breeding programmes involving marker assisted selection of innately pathogen resistant strains of rainbow trout rely on reliable controlled infection studies, extensive DNA typing of individual fish and recording of expression of relevant genes. We exposed juvenile rainbow trout (6 h bath to 2.6 × 10 5  CFU mL −1 ) to the fish pathogen Yersinia ruckeri serotype O1, biotype 2, eliciting Enteric Red Mouth Disease ERM, and followed the disease progression over 21 days. Cumulative mortality reached 42% at 12 days post challenge (dpc) after which no disease signs were recorded. All fish were sampled for DNA-typing (50 k SNP chip, Affymetrix®) throughout the course of infection when they showed clinical signs of disease (susceptible fish) or at day 21 when fish showed no clinical signs of disease (survivors - resistant fish). Genome-wide association analyses of 1027 trout applying single nucleotide polymorphisms (SNPs) as markers revealed an association between traits (susceptible/resistant) and certain regions of the trout genome. It was indicated that multiple genes are involved in rainbow trout resistance towards ERM whereby it is considered a polygenic trait. A corresponding trout group was kept as non-exposed controls and a comparative expression analysis of central innate and adaptive immune genes in gills, spleen and liver was performed for three fish groups: 1) moribund trout exhibiting clinical signs 7 dpc (CS), 2) exposed fish without clinical signs at the same sampling point (NCS) and 3) surviving fish at 21 dpc (survivors). Immune genes encoding inflammatory cytokines (IL-1β, IL-2A, IL-6A, IL-8, IL-10A, IL-12, IL-17A/F2A, IL-17C1, IL-17C2, IL-22, IFNγ, TNFα), acute phase reactants (SAA, C3, cathelicidins, lysozyme) were expressed differently in CS and NCS fish. Correlation (negative or positive) between expression of genes and bacterial load suggested involvement of immune genes in protection. Down-regulation of adaptive immune genes including IgDm, IgDs, IgT and TCR-β was seen primarily in CS and NCS fish whereas survivors showed up-regulation of effector molecule genes such as cathelicidins, complement and lysozyme suggesting their role in clearing the infection. In conclusion, SNP analyses indicated that ERM resistance in rainbow trout is a multi-locus trait. The gene expression in surviving fish suggested that several immune genes are associated with the trait conferring resistance. Highlights: SNP analyses of rainbow trout indicated that resistance against Yersinia ruckeri is a polygenic trait. Expression of immune relevant genes different significantly between resistant and susceptible trout. Trout surviving the infection exhibited upregulated genes encoding innate effector molecules.